Characterization of drought propagation over the Tibetan Plateau - Di Wu; Zeyong Hu (Journal of Hydrology: Regional Studies)
Study region: This study was carried out on the Tibetan Plateau (TP), which contains multiple important ecosystems, is the source of many rivers in China, and is experiencing significant climate change. Study focus: Clarifying drought propagation characteristics is crucial for understanding the mechanism of drought development and benefiting drought mitigation and early warning schemes. However, there is currently a notable lack of research on droughts on the TP and drought propagation characteristics on the TP have yet to be investigated. In this study, we investigated drought propagation time, probability, threshold, and the climatic factors associated with drought development based on the copula probability model and correlation, Bayesian network, and attribution analyses, allowing us to fill current research gaps. New hydrological insights for the region: The research framework proposed in this study effectively reflected the characteristics of drought propagation. Our results showed that seasonality and aridity controlled the propagation time from meteorological drought (MD) to agricultural drought (AD), i.e., the time was shortest in summer (2.311.0 months) and in the humid zone (2.37 months); the same pattern was found for the propagation of MD to hydrological drought (HD), with the propagation time being 2.33.0 months in summer and 2.36 months in humid zones. The propagation probability for both AD and HD generally increased synchronously with the severity of MD, and also exhibited seasonal patterns, with the highest probability values in summer (0.590.90 for AD and 0.510.82 for HD). The highest propagation thresholds were also found in summer (−1.68 to −1.09 for AD and −1.68 to −1.36 for HD). The trends of both propagation time and probability were significant, and the probability of HD exhibited significant downward trends (−0.074 to −0.030/decade) across the TP. Precipitation was the dominant factor controlling the development of drought in most cases; however, other climatic factors, such as maximum temperature, solar radiation, and specific humidity, contributed 14.0 %43.9 % of the variances of AD and HD.